Abandoning the EPP-feature in Polish dual copula clauses by redefining the predication relation - Rafał Jurczyk (LingBaW)
This paper questions the logic behind the presence and the working of the EPP-feature in Polish dual copula clauses (henceforth, DCCs) with the pronominal copula to, the verbal copula być ‘to be’, and two nominative 3rd person DPs, as represented in Bondaruk (2019). The criticism follows from: (i) – Chomsky’s (2000, 2001) downward Agree operation; (ii) – the view that the predicator encodes the predication relation between the pre-copular subject and the post-copular predicate; (iii) – selective multiple Agree, whereby the satisfaction of the EPP- and uφ-features is divorced. Adopting (i)–(iii), Bondaruk’s scrutiny allows either the pre- or the post-copular DP to occupy SpecTP, thereby accounting for DCCs’ agreement and configurational patterns, but, simultaneously, suffering from theoretical shortcomings it creates. We argue for a simpler satisfaction of the subject requirement which does not rely on the troublesome EPP-feature, but is motivated formally by the relation between T and the higher DP. We derive this requirement by following Zeiljstra’s (2012) upward Agree which only takes place once interpretable features c-command uninterpretable features, and Rothstein’s (2004) approach which is based on a neo-Davidsonian event semantics and which argues that be and its complement form a complex predicate, separated from the pre-copular DP both semantically and syntactically.